Subacute Toxicity Test of Cocoa Bean Extract (Theobroma cacao L.) on Mice (Mus musculus L.) - Hendri Poernomo; Setiawan (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Cocoa is one of the plants that is believed to have many health benefits and is used in herbal medicine so it is necessary to test the safety of its use. The purpose of the study was to determine abnormalities in the hepatic histopathology of mice that occurred after repeated administration of the test preparation. Materials and Methods: The research used in vivo laboratory experiments with the post-test only control group approach. The samples used were 25 consisting of 5 groups, namely the group of mice given cocoa bean extract at a dose of 4500 mg/kgBB, 5500 mg/kgBB, 6500 mg/kgBB, 7500 mg/kgBB, and the control group was given distilled water, and for the allergy test was given 32% cocoa bean extract gel. Oral administration of the test preparation was carried out every day for 28 days, once a day. Observations included toxic symptoms by looking at hepatic organ histopathology. Data analysis used Kruskal Wallis test followed by Mann Whitney test for subacute toxicity test. Results and discussion: showed that the administration of cocoa bean extract at doses of 4500 mg/kgBB, 5500 mg/kgBB, 6500 mg/kgBB, and 7500 mg/kgBB had an effect on subacute toxicity at the time of administration to mice which caused the death of mice and affected the hepatic histopathology of mice. Conclusion: The conclusion is that cocoa bean extract at certain doses has an effect on subacute toxicity in mice.